2015
DOI: 10.1016/j.virol.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing and development of an expression microarray platform for liver infection in adenovirus type 5-infected Syrian golden hamsters

Abstract: The Syrian golden hamster is an attractive animal for research on infectious diseases and other diseases. We report here the sequencing, assembly, and annotation of the Syrian hamster transcriptome. We include transcripts from ten pooled tissues from a naïve hamster and one stimulated with lipopolysaccharide. Our data set identified 42,707 non-redundant transcripts, representing 34,191 unique genes. Based on the transcriptome data, we generated a custom microarray and used this new platform to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 73 publications
4
18
0
Order By: Relevance
“…injection of Ad5. We found that about 20% of transcripts were up-or downregulated, with prominent upregulation of genes involved in the innate immune response to virus infection (36). The latter finding is consistent with our recent study in Syrian hamsters with the STAT2 gene knocked out (STAT2 KO hamsters).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…injection of Ad5. We found that about 20% of transcripts were up-or downregulated, with prominent upregulation of genes involved in the innate immune response to virus infection (36). The latter finding is consistent with our recent study in Syrian hamsters with the STAT2 gene knocked out (STAT2 KO hamsters).…”
supporting
confidence: 92%
“…To further develop the Syrian hamster as a model, we (36) and others (37) have sequenced the Syrian hamster transcriptome. We identified 42,707 unique transcripts representing 34,191 unique genes.…”
mentioning
confidence: 99%
“…Although the historical lack of immune reagents for hamsters has resulted in a relatively poor understanding of basic hamster immunology, a number of recently developed research tools—including the hamster transcriptome and kinome4748, microarray platforms49, and RT-qPCR assays to measure the host response17—are poised to increase the value of hamsters as an animal model. In addition, together with the EHF hamster model, the MHF hamster model will contribute to both basic and translational research for the development of medical countermeasures such as pan-filovirus therapies and bivalent vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…HapT1 cells were incubated with FITC-conjugated anti-mouse/rat MHC Class II antibody (I-Ek; clone 14-4-4 S, eBioscience) 49 for 1 h and fixed in 4% paraformaldehyde for 5 min, and analyzed on BD Accuri C6.…”
Section: Flow Cytometric Analysesmentioning
confidence: 99%